Leadership Perception and Work Engagement: A Bibliometric Analysis of Research Trends and Intellectual Structure (2021–2025) - Pipi Yuniarti (MUNIF: International Journal of Religion Moderation, 2026)
This study aims to analyze the development of literature on leadership perception and work engagement during the 2021–2025 period. Despite the growing number of publications on leadership perception and work engagement, previous studies have largely focused on empirical relationships between the two constructs, while comprehensive mapping of their intellectual structure, thematic evolution, and emerging research directions remains limited. This study addresses that gap by providing a systematic bibliometric overview of the field. The method employed is a bibliometric analysis using VOSviewer version 1.6.21 software. The data population was retrieved from the Dimensions database using relevant keywords and screened via the PRISMA framework, resulting in a final sample dataset instrument of 262 original journal articles. The results indicate a consistently rising annual publication trend, growing from 20 articles in 2021 to 99 articles in 2025. Conceptual structure analysis identified three major clusters, with leadership, work engagement, and transformational leadership emerging as the core concepts dominating the literature. Regarding the intellectual structure, Ronald J. Burke was identified as the most central reference author, serving as a conceptual bridge between different research streams. The thematic evolution analysis revealed a shift from an individual behavior focus toward broader institutional issues. Topics such as sustainability, workplace spirituality, implementation, and city government emerged as cutting-edge themes with low research density, presenting open opportunities for future exploration. These findings establish a systematic foundation for future research agendas, particularly in integrating value-based leadership within specific organizational contexts like Islamic Higher Education Institutions (PTKI).